2014
DOI: 10.1016/j.appet.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A brief intervention increases fruit and vegetable intake. A comparison of two intervention sequences

Abstract: A B S T R A C T Background and Purpose:To evaluate the effectiveness of two subsequent intervention components (motivational and self-regulatory components), placed in different order, to promote fruit and vegetable (FV) intake. Methods: After baseline assessment, university students (N = 205, aged 18-26 years) were allocated to two groups. One group received a motivational intervention (outcome expectancies, risk perception, and task self-efficacy) followed by a self-regulatory intervention (planning and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 27 publications
1
24
1
6
Order By: Relevance
“…Our findings support those of other studies that suggest that planning is an effective way to help adolescents to change their health behaviours, including F&V intake Lhakhang et al, 2014;Verhoeven et al, 2012). However, evidence suggests that it is important to ensure that individuals are motivated before they are provided with volitional strategies and techniques (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings support those of other studies that suggest that planning is an effective way to help adolescents to change their health behaviours, including F&V intake Lhakhang et al, 2014;Verhoeven et al, 2012). However, evidence suggests that it is important to ensure that individuals are motivated before they are provided with volitional strategies and techniques (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Although some researchers have found that perceptions of risk have a negligible impact on F&V intake (Schwarzer et al, 2007), many studies suggest that risk perceptions have a significant, albeit relatively small, correlation with intention and behaviour and can influence behaviour, especially if coupled with specific recommendations on how to reduce the risk (for a review, see Sheeran et al, 2014). Outcome expectancies reflect the individuals' consideration of the pros and cons of performing the respective behaviour (Lhakhang et al, 2014;Schwarzer, 2008). Self-efficacy is the individuals' confidence in his/her ability to perform the intended behaviour (e.g.…”
Section: The Health Action Process Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Ressaltam-se questões financeiras relacionadas com a saída do jovem da casa da família para estudar, estresse com as atividades acadêmicas, ausência de tempo para uma maior dedicação à produção da sua própria alimentação e/ou atenção a horários, falta de habilidade para cozinhar e de conhecimento de nutrição para realização de escolhas mais saudáveis, conforme apresentado anteriormente (33)(34)(35) . Através dos estudos selecionados para o presente artigo, as estratégias que melhor apresentaram resultados para mudança de comportamento nessa população e seus principais limitantes foram observadas.…”
Section: Discussionunclassified
“…(35) Implementar o programa FRESH (Recursos alimentares e educação para saúde em universitários), objetiva melhorar a alimentação no campus e promover comportamentos saudáveis entre os estudantes.…”
Section: Critérios De Inclusão Artigos Original Idiomas: Inglês/espanunclassified